2009
DOI: 10.14214/sf.464
|View full text |Cite
|
Sign up to set email alerts
|

Regional energy wood logistics – optimizing local fuel supply

Abstract: The promotion of electric energy production from solid biomass by the Austrian government has lead to a boom in the construction of new combined heat and power plants. The current total demand for wood chips in the research area for energy purposes is 70 400 m 3 of loose volume chips per year. The expected increase in demand due to these new plants is more than 4 times greater than current demand: up to 302 700 m 3 of loose volume per year. Even if the energy wood feedstock potential is satisfactory, the desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(55 citation statements)
references
References 16 publications
1
53
0
1
Order By: Relevance
“…At the roadside, the raw material is chipped with either a truck mounted or tractor-based chipper directly into the chip truck. Only in some cases, for example in the Alps, chips are blown into a pile on the ground (Kanzian et al 2009). Chipping at a plant or terminal usually results in lower chipping costs, but increases the overall demand on logistics and handling costs, and is often not possible due to high dust and noise emmissions (Kanzian et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…At the roadside, the raw material is chipped with either a truck mounted or tractor-based chipper directly into the chip truck. Only in some cases, for example in the Alps, chips are blown into a pile on the ground (Kanzian et al 2009). Chipping at a plant or terminal usually results in lower chipping costs, but increases the overall demand on logistics and handling costs, and is often not possible due to high dust and noise emmissions (Kanzian et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Combining geographic information systems (GIS) and Linear Programming has been studied by Kanzian et al (2009) in order to optimise the supply through the use of terminals. In Austria wood energy supply is required constantly through the year especially in winter when conditions often make mountainous regions inaccessible.…”
mentioning
confidence: 99%
“…Together with Eriksson & Bjoerheden (1989) and Gunnarsson et al (2004) the authors have concluded that direct supply (without the use of intermediate terminals) is the most efficient and economical way to supply fuels to heating and power plants. Although the use of terminals can improve the quality of the biomass by minimising the MC and therefore increasing the energy content, it does not pay off the cost of making them part of the supply chain (Kanzian et al 2009).…”
mentioning
confidence: 99%
“…After conducting a GIS analysis, the new attribute can be imported into the segment attribute table for further use in calculations. The next steps might be further studies utilising road map data to calculate the supply cost by optimising the biomass flow from the stands to the plants (see, for example, Ranta 2005;Kanzian et al 2009). More accurate and detailed stand inventory data would make it possible to simulate the development and operations for the stands and optimise forest management (Rørstad et al 2010).…”
Section: Discussionmentioning
confidence: 99%